Syntheses, crystal structure and biological evaluation of three novel Cu (II) complexes with Schiff base derived from fluorinated amino acid and Salicylaldehyde. (28th October 2019) - Wu, Ruixue; Bi, Caifeng; Zhang, Xia; Zong, Ziao; Fan, Chuanbin; Zhang, Xiaoyin; Li, Nana; Fan, Yuhua
Abstract : Three novel Cu (II) coordination complexes, formulated as [Cu3 (C14 H8 NO3 F)2 (CH3 COO)2 ]n (1 ), [Cu2 (C14 H9 NO3 F)2 (CH3 COO)Cl] (2 ) and [Cu(C14 H8 NO3 F)(CH3 OH)2 ] (3 ), have been synthesized by 3‐Fluoroanthranilic acid, Salicylaldehyde and Cu (II) salt as sources in different reaction conditions and characterized by single crystal X‐ray diffraction, X‐ray powder diffraction, IR spectroscopy and elemental analysis. Single‐crystal diffraction analysis revealed that the complexes exhibited different coordination modes and conformations which were linked into multidimensional networks through some weak interactions. The biological activities vary greatly on account of the different Cu (II) numbers among the three complexes. In order to discuss the bioactivities, the complexes have been screened for antimicrobial activities against E. coli and S. aureus, antitumor activities against A549 (human lung cancer cells), Hela (human cervical cancer cells) and HepG‐2(human liver hepatocellular carcinoma cells). Their interactions with calf thymus DNA were investigated by UV–visible and fluorescence spectrometry, as well as viscosity measurements. Interestingly, 1 (the rare 3‐core Cu (II) coordination polymer) shows great antibacterial activities and highest DNA binding affinities. Antitumor studies revealed that complex 1 also exhibited highest activity. Abstract : Three novel Cu(II) complexes with Schiff base derived from fluorinated amino acid and Salicylaldehyde were synthesized in different conditions and characterized by several necessary methods. The biological activities vary greatly on account of the different Cu(II) numbers and some of them show great antum or activities and highest DNA binding affinities. All the results might facilitate the understanding of the interactions between DNA and such complexes and be significant for the design of new antineoplastic agents.